WEB ADAPTIF MENGGUNAKAN ALGORITMA FREQUENT WEB DOCUMENT PATTERN (FWDP) PADA WEBSITE UNIVERSITAS RESPATI - Listiawan, Indra (Universitas Respati Yogyakarta, 2012)
An Institution Website is a profile of an institution for the people who directly or indirectly related to the agency. Some problems related to the performance of a web are the speed and accuracy of presentation of the information needed by the community.Technology of adaptive Website is one of technology that attempted to simplify the user to find the information that need from a website. The technology is based on web log. Log is used as a reference for the access patterns are realized in the form of recommendations links to information that is often accessed by people from the website. Log data processing performed by implemented the FWDPTree algorithm to get a particular tree structure that stores information page along with the frequency of occurrence, then performed datamining by algorithm FWDP-mine.This Technology has been able to reach information more quickly There are still weaknesses in this system. The adaptive system has not been able to make the process of adaptation in realtime, this is due to the need for time to process large log data in order to obtain the user's access patterns, while the session that occurred during the offline process does not processed. Keywords— Adaptive web, Data Log, FWDP Algorithm, Association Rule, Realtime